(untitled) (Ius Novum, 2018)
The author shows, on the basis of an analysis of the existing rules of criminal procedure, how the present authorities perceive a prosecutor. The adversarial model of criminal proceedings, which has been rejected by the present authorities, is a counterpoint to the existing rules. The analyses show a negative image of a prosecutor as a body unable to prove the accused party’s guilt and to undermine the presumption of innocence that protects the accused. The image of a prosecutor as perceived by the present authorities is very unfavourable to him. Therefore, it is in the interest of prosecutors to change this situation.